Aberrant Hypermethylation-Mediated Suppression of PYCARD Is Extremely Frequent in Prostate Cancer with Gleason Score ≥ 7. (4th February 2021) - Miyauchi, Toshiya; Takahashi, Masahiro; Mitsuzuka, Koji; Saiki, Yuriko; Okubo, Teppei; Vertino, Paula M.; Goto, Akiteru; Arai, Yoichi; Horii, Akira; Fukushige, Shinichi
Abstract : Epigenetic gene silencing by aberrant DNA methylation leads to loss of key cellular pathways in tumorigenesis. In order to analyze the effects of DNA methylation on prostate cancer, we established LNCaP-derived human prostate cancer cells that can pharmacologically induce global reactivation of hypermethylated genes by the methyl-CpG targeted transcriptional activation (MeTA) method. The MeTA suppressed the growth of LNCaP-derived cells and induced apoptosis. Microarray analysis indicated that PYCARD (PYD and CARD domain containing) encoding an apoptosis-inducing factor was upregulated by 65-fold or more after treatment with MeTA. We analyzed DNA methylation statuses using 50 microdissected primary prostate cancer tissues and found an extremely high frequency of tumor-specific promoter hypermethylation of PYCARD (90%, 45/50). Moreover, DNA methylation status was significantly associated with Gleason score (P = 0.0063 ); the frequency of tumor-specific hypermethylation was 96% (44/46) in tumors with Gleason score ≥ 7, whereas that in tumors with Gleason score 6 was 25% (1/4). Immunohistochemical analyses using these 50 cases indicated that only 8% (4/50) of cancerous tissues expressed PYCARD, whereas 80% (40/50) of corresponding normal prostate epithelial and/or basal cells expressed PYCARD. In addition, there was no relationship between PYCARD immunostaining and the Gleason score in cancerous tissue and surrounding normal tissue. Inducible expression of PYCARD inhibited cell proliferation by induction of apoptosis. These results suggest that aberrant methylation of PYCARD is a distinctive feature of prostate cancers with Gleason score ≥ 7 and may play an important role in escaping from apoptosis in prostatic tumorigenesis.